Alternative Splicing and Its Impact as a Cancer Diagnostic Marker - Yun-Ji Kim; Heui-Soo Kim (Genomics & Informatics)
Most genes are processed by alternative splicing for gene expression, resulting in the complexity of the transcriptome in eukaryotes. It allows a limited number of genes to encode various proteins with intricate functions. Alternative splicing is regulated by genetic mutations in cis-regulatory factors and epigenetic events. Furthermore, splicing events occur differently according to cell type, developmental stage, and various diseases, including cancer. Genome instability and flexible proteomes by alternative splicing could affect cancer cells to grow and survive, leading to metastasis. Cancer cells that are transformed by aberrant and uncontrolled mechanisms could produce alternative splicing to maintain and spread them continuously. Splicing variants in various cancers represent crucial roles for tumorigenesis. Taken together, the identification of alternative spliced variants as biomarkers to distinguish between normal and cancer cells could cast light on tumorigenesis.